THE EFFECT OF SERVICE QUALITY AND SATISFACTION ON LOYALTY IN MEMBERS OF “KSPPS BMT MANDIRI SEJAHTERA JAWA TIMUR” - Ferdian Dwi Krismonicha; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKPenelitian bertujuan mengetahui kualitas pelayanan dan kepuasan berpengaruh terhadap loyalitas anggota “KSPPS BMT Mandiri Sejahtera Jawa Timur” secara parsial dan simultan dengan data dari hasil kuisioner secara aksidental dengan sampel 100 anggota BMT dan diuji instrumen. Pengujian regresi berganda Y = a + b1.x1 +b2.x2 menghasilkan persamaan regresi berganda Y = 3,793 + 0,316 + 0,477, uji asumi klasik (normalitas multikoliniearitas, heteroskedastistas), dan uji hipotesis berdasar uji T ditemukan hipotesis pertama dan kedua diterima, kualitas pelayanan dan kepuasan masing-masing memengaruhi loyalitas dengan kualitas pelayanan lebih dominan mempengaruhi loyalitas. Hasil simultan hipotesis uji F kedua variabel bersama-sama berpengaruh terhadap loyalitas.Kata Kunci: Kualitas Pelayanan, Kepuasan, Loyalitas, Baitul Maal Tamwil. ABSTRACTThe purpose of the study is to find out whether service quality and satisfaction affect the loyalty of members of "KS PPS BMT Mandiri Sejahtera East Java" partially and simultaneously with data from the accidental questionnaire results, with a sample of 100 BMT members and tested by using some instruments. The multiple regression test of Y = a + b1.x1 +b2.x2 gave the multiple regression equation of Y = 3.793 + 0.316 + 0.477, and classic assumption test (multicollinearity normality, heteroscedasticity), and hypothesis testing based T- test found that the first and second hypotheses are accepted, and service quality and satisfaction each influence loyalty with service quality more dominantly affects loyalty. The simultaneous results of the two variables of F test hypothesis together have an effect on loyalty.Keywords: Service Quality, Satisfaction, Loyalty, Baitul Maal Tamwil REFERENCESAnshori, M., & Iswati, S. (2009). Metodologi penelitian kuantitatif. Surabaya: Airlangga University Press (AUP).Berry, L. L., Parasuraman, A., & Zeithaml, V. A. (1988). SERVQUAL: A multiple-item scale for measuring consumer perceptions of service quality. Journal of Retailing, 64(1), 12–40.Fida, B. A., Ahmed, U., Al-Balushi, Y., & Singh, D. (2020). Impact of service quality on customer loyalty and customer satisfaction in Islamic banks in the Sultanate of Oman. SAGE Open, 10(2). https://doi.org/10.1177/2158244020919517Griffin, J. (2002). Customer loyalty. Jakarta: Erlangga.Huda, N., & Heykal, M. (2010). Lembaga keuangan Islam, Jakarta: Kencana.Ilieska, K. (2013). Customer satisfaction index – as a base for strategic marketing management. TEM Journal, 2(4), 327–331.Kotler, P., & Keller, K. L. (2008). Manajemen pemasaran. Jakarta: Penerbit Erlangga.Leninkumar, V. (2017). The relationship between customer satisfaction and customer trust on customer loyalty. International Journal of Academic Research in Business and Social Sciences, 7(4), 450–465. https://doi.org/10.6007/ijarbss/v7-i4/2821Omoregie, O. K., Addae, J. A., Coffie, S., Ampong, G. O. A., & Ofori, K. S. (2019). Factors influencing consumer loyalty: Evidence from the Ghanaian retail banking industry. International Journal of Bank Marketing, 37(3), 798–820. https://doi.org/10.1108/IJBM-04-2018-0099Parasuraman, A., Zeithaml, V. A., & Berry, L. L. (1985). A conceptual model of service quality and its implications for future research. Journal of Marketing, 49(4), 41. https://doi.org/10.2307/1251430Sunyoto, D. (2012). Dasar-dasar manajemen pemasaran. Yogyakarta: CAPS.Yap, B. W., Ramayah, T., & Wan Shahidan, W. N. (2012). Satisfaction and trust on customer loyalty: A PLS approach. Business Strategy Series, 13(4), 154–167. https://doi.org/10.1108/17515631211246221Zeithaml, V. A. (2000). Service quality, profitability, and the economic worth of customers: What we know and what we need to learn. Journal of the Academy of Marketing Science, 28(1), 67–85. https://doi.org/10.1177/0092070300281007Zeithaml, V. A., Berry, L. L., & Parasuraman, A. (1996). The behavioral consequences of service quality. Journal of Marketing, 60(2), 31–46. https://doi.org/10.2307/1251929